(untitled) (World Science, 2020)
Skovoroda’s philosophy is considered through the prism of philosophical ideas and features of the scientific discourse presented by the modern philosophers, in particular René Descartes. Special attention is paid to the similarity of these philosophers’ views, who focus their attention of the method of self-cognition. However, Descartes engages in the gnosiological aspect and pays attention to the process of cognition and on the correctness of conclusions. Whereas Skovoroda is concentrated on ontology or even on metaphysics speaking not so much about the process of cognition, but about the essence of existence. Besides this it is important that both thinkers have the same world-view intuition, in particular Skovoroda, akin to Descartes, considers God to be the only source of final and absolute truth.